Satisfação no trabalho do professor de educação física (Revista Paulista de Educação Física, 1998)
The purpose of this study was to compare the level of job satisfaction and the meaning of the job expressed by physical education teachers and teacher of other subjects. The study verified whether physical education teachers would express a degree of satisfaction differently from those expressed by teachers of other subjects (mathematics and Portuguese), which are traditionaly well valued in school. 236 teachers took part in this study: 113 from physical education, 62 from mathematics and 61 from Portuguese working in Sao Paulo elementary and secondary schools. Data analysis was carried out by running t-test and One Way ANOVA both taking p < 0.05. The analyses indicated that: a) there was a significant difference in job satisfaction scores (t = 2.01; p = 0.045; to gl = 234), a trend in which Physical Education teachers (189.80) showed more satisfaction at work than colleagues in others subjects (184.63); b) no significant difference was found for meaning attributed to the job (t = 0.95; p = 0.344; to gl = 234). The results were somewhat unexpected due to concerns about the lack of understanding on the role and goals of Physical Education in school